2017
DOI: 10.1093/dote/dox082
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies in recurrent esophageal or junctional cancer

Abstract: Little evidence is available about survival rates in patients with recurrent disease after potentially curative surgery for esophageal or junctional cancer. Only in limited occasions, potentially curative salvage strategies are available. The aim of this study is to analyze survival rates and patterns of dissemination, and to identify independent prognostic factors in a consecutive series of patients who develop recurrent esophageal or junctional cancer. Between 1994 and 2015, patients who developed disease re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…In the present study, isolated locoregional recurrence was found in 13 of 42 patients (31 per cent) who were regularly followed up with EUS and PET–CT, a figure slightly higher than the 23 per cent reported elsewhere 6 , probably related to the more frequent examinations in the present study. In a recent study of oesophageal and GOJ cancers 32 , in which patients underwent imaging only if recurrence was suspected clinically, isolated local recurrence was found in only 10 per cent. It may be that this pattern of recurrence is not necessarily symptomatic and the time window for its detection can easily be missed.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, isolated locoregional recurrence was found in 13 of 42 patients (31 per cent) who were regularly followed up with EUS and PET–CT, a figure slightly higher than the 23 per cent reported elsewhere 6 , probably related to the more frequent examinations in the present study. In a recent study of oesophageal and GOJ cancers 32 , in which patients underwent imaging only if recurrence was suspected clinically, isolated local recurrence was found in only 10 per cent. It may be that this pattern of recurrence is not necessarily symptomatic and the time window for its detection can easily be missed.…”
Section: Discussionmentioning
confidence: 97%
“…An earlier diagnosis, however, may not have a large effect on the prognosis, as treatment options after recurrence are limited and postrecurrence survival is poor. 23 , 24 To assess the true value of the addition of nivolumab in the adjuvant setting, overall survival data are eagerly awaited.…”
Section: Discussionmentioning
confidence: 99%
“…Yuichiro and colleagues ( 22 ) reported that the median duration of survival of patients suffering from esophageal cancer with local recurrence after surgery was ~178 days. According to Butterer and colleagues, the median overall survival of patients with local recurrence was 4.9 months, that of patients with distant metastasis was 2.9 months, and that of all patients was 3.2 months ( 23 ).…”
Section: Discussionmentioning
confidence: 99%